The multiplier effect of mentorship in policy-relevant research - Desai, Bina; Taiwo, Ibukun (2025)
This is Part 2 of a blog series on Building Local Research Capacity through Time, Trust, and Knowledge Transfer. In this edition, we unpack the real costs and inputs of mentorship and how these investments translate into measurable outcomes, giving a clear picture of the “cost curve” from mentorship to impact.